2005
DOI: 10.1093/aob/mci133
|View full text |Cite
|
Sign up to set email alerts
|

Applicability and Limitations of Optimal Biomass Allocation Models: A Test of Two Species from Fertile and Infertile Habitats

Abstract: The applicability of optimal biomass allocation models is fairly high, although constraints in the plasticity of biomass allocation could prevent optimal regulation of the root : leaf ratio in some species. The assumption that regulation of the root : leaf ratio enables maximization of RGR was supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 41 publications
(73 reference statements)
4
18
0
1
Order By: Relevance
“…This agrees with optimal biomass allocation models (Osone and Tateno 2005), i.e. seedlings adjust biomass allocation in response to environment stress.…”
Section: Seedlings Can Survive In Low Salinitysupporting
confidence: 87%
“…This agrees with optimal biomass allocation models (Osone and Tateno 2005), i.e. seedlings adjust biomass allocation in response to environment stress.…”
Section: Seedlings Can Survive In Low Salinitysupporting
confidence: 87%
“…Our results suggest a higher plasticity in N use efficiency for low N accession plants as compared to plants from high N regions. These findings are in agreement with an earlier study by Osone and Tateno (2005) who reported reduced plasticity in biomass allocation (R/S ratio) for plants from fertile soils as compared to plants from infertile soils. According to Bloom et al (1985), plants act similarly to economic theorems maximizing their efficiency and optimal resource allocation.…”
Section: Effects Of Accession On the Response To Nitrogensupporting
confidence: 93%
“…As already suggested by Vergeer et al (2008), plants have the potential to adapt to long term changes in N exposure and it was suggested that this adaptive response may evolve at the cost of plasticity (see also Osone and Tateno 2005). Indeed Useche and Shipley (2010) found that plasticity in root biomass production was adaptive and related to relative growth rate (RGR).…”
Section: Implications Of These Resultsmentioning
confidence: 86%
“…These patterns suggest that both leaf gas exchange and plant hydraulic capacity are determined by the root system morphology. A higher SRL has been associated with a higher nitrogen absorption rate, which, in turn, is correlated with plant functional responses as increases in maximum relative growth rate (Osone and Tateno 2005). The positive correlation between SRL and K As indicates that the root systems characterized by less massive roots per unit length have a higher hydraulic conductance.…”
Section: Morphological Traits Among Speciesmentioning
confidence: 99%